Developing a Frame Independent Modular System (FIMS) applied to a Philippine context for obsolescence avoidance and market flexibility - Capistrano, Edmond Joseph E.; Joson, Gerard Thomas F. (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
Modularity is a concept consistently applied in the field of architecture as seen in the bricks that make up any wall up to the massive blocks that constitute entire ships. However, the field has yet to employ modularity’s potential on a scale and matter of reusability that could make an effective impact. This design thesis attempts to apply modularity under the terms of architecture and not merely as units for construction, to be known as Architectural Modularity. Modularity is explored in its full capability to be used and reused and to be flexible for a variety of functions given the context. This flexibility in modular systems is integral to pursuing agendas in building lifespan sustainability for projects without compromising the needs of the users as the market changes over time. For this modular capability, this design develops a system that could be employed under multiple site scenarios with care given to the users and logistics involved. A system of critique was developed to identify sites for initial projects as to reduce the blow of introducing a new system of and market for real estate. Upon the identification of the site the developed design took into consideration the necessary allocations and issues on flexibility through iterative processes and development such as crane schemes, maintenance allocation, population density in contemporary models and structural considerations among many more. The final design schematic presented would hopefully spur further research and development of Modular Architecture in the many fields that would be required to make it a reality.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
includes appendices
Keywords: Modular architecture